DESAIN STRUKTUR TEMPAT EVAKUASI SEMENTARA TSUNAMI DI BENGKULU - Alfiansa Bayu Pradana; Riko Pratama Saputra; Himawan Indarto; Ilham Nurhuda (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Several places in Indonesia have high vulnerability of tsunami. It can be seen from the facilities and infrastructures damages on several coastal areas caused by tsunami. Itcauses many victims. To minimize the risk of victims while tsunami occurs, need to prepare the rescuing strategies. One of those is providing temporary evacuation places for the coastal areas that can protect the local society from tsunami, including them are hidrodinamis, the buoyant force, hidrodinamik and impulsive, collision, lift hidrodinamik, and effects damming of debris is carried away water.In order to anticipate the tsunami, the temporary shelter should be designed to resist tsunami and earthquake loading.